2008
DOI: 10.1371/journal.pntd.0000256
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Infections of Poverty in the United States of America

Abstract: In the United States, there is a largely hidden burden of diseases caused by a group of chronic and debilitating parasitic, bacterial, and congenital infections known as the neglected infections of poverty. Like their neglected tropical disease counterparts in developing countries, the neglected infections of poverty in the US disproportionately affect impoverished and under-represented minority populations. The major neglected infections include the helminth infections, toxocariasis, strongyloidiasis, ascaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
288
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 306 publications
(296 citation statements)
references
References 123 publications
(176 reference statements)
1
288
2
5
Order By: Relevance
“…Nevertheless, immigrant pregnant women may have been infected before they came to Taiwan and should not be ignored. Of note, toxoplasmosis is considered an infection associated with poverty even in the United States (26). A considerable number of studies have indicated that several factors can explain the wide variation in the the seroprevalence of toxoplasmosis in humans between countries and often within a specific country or between different communities in the same region, including dietary habits, socioeconomic status, cultural habits, quality of water, and sanitation coverage (7,27).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, immigrant pregnant women may have been infected before they came to Taiwan and should not be ignored. Of note, toxoplasmosis is considered an infection associated with poverty even in the United States (26). A considerable number of studies have indicated that several factors can explain the wide variation in the the seroprevalence of toxoplasmosis in humans between countries and often within a specific country or between different communities in the same region, including dietary habits, socioeconomic status, cultural habits, quality of water, and sanitation coverage (7,27).…”
Section: Discussionmentioning
confidence: 99%
“…CMV infection has been considered a disease of poverty and continues to be strongly patterned by socioeconomic status in the US and globally (Hotez 2008;Manicklal et al 2013). Indeed, there is a substantial body of evidence suggesting that CMV is socioeconomically (e.g., educational attainment and income) patterned across the life course.…”
Section: Social and Economic Determinants That Influence CMV Epidemiomentioning
confidence: 99%
“…The associations may reflect increased exposure to CMV among individuals who are living in disadvantaged settings, which may be more likely to be characterized by overcrowding, lack of access to hygiene and sanitation resources, and increased use of daycare at earlier ages, which have all been implicated in increased transmission of CMV as well as many other infectious diseases (Hotez 2008;Manicklal et al 2013). At the same time, there is evidence that individuals of lower socioeconomic status are burdened by a higher force of CMV infection at earlier ages, measured by the instantaneous per capita rate of CMV acquisition by age (Colugnati et al 2007).…”
Section: Social and Economic Determinants That Influence CMV Epidemiomentioning
confidence: 99%
“…With respect to the concept of NTDs disproportionately affecting the poor living in wealthy countries, I have noted a high level of these diseases concentrated in areas of extreme poverty in the United States, especially the southern United States and the U.S. Gulf Coast (22,23). For instance, today NTDs such as Chagas disease, cysticercosis, dengue fever and toxocariasis can be found in U.S. areas of poverty, where they disproportionately affect people of color (22,23).…”
Section: A National School Of Tropical Medicine In Houstonmentioning
confidence: 99%
“…For instance, today NTDs such as Chagas disease, cysticercosis, dengue fever and toxocariasis can be found in U.S. areas of poverty, where they disproportionately affect people of color (22,23). Some of them may be adversely affecting childhood cognitive development among the poor, thereby reinforcing poverty (24).…”
Section: A National School Of Tropical Medicine In Houstonmentioning
confidence: 99%